PENGEMBANGAN WEBSITE PEMBELAJARAN BERBANTUAN CHATBOT AI PADA MATA PELAJARAN PEMROGRAMAN BERORIENTASI OBJEK UNTUK SISWA SMK - Wanda Ramansyah; Nawafilillah Nawafilillah; Tania Adela Sapitri (Department of Science and Technology Ibrahimy University, 2026)
Object-Oriented Programming (OOP) is an essential subject for Vocational High School (SMK) students in the Software and Game Development (PPLG) program as preparation for competencies in the software development field. However, the implementation of OOP learning at SMK Al-Aziziyah Kwanyar still faces several challenges, including limited learning media, the dominance of conventional teaching methods, and limited instructional time for teachers to provide individual assistance to students. This study aims to develop a chatbot AI-assisted learning website for the Object-Oriented Programming subject as an interactive, flexible, and personalized learning solution. This research employed a Research and Development method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The developed product is a learning website equipped with learning materials, reading resources, assignments, learning management features, and an AI-based chatbot as a virtual learning assistant. The material expert validation results showed a feasibility percentage of 94.6%, while media expert validation reached 93.3%, both categorized as very feasible. User testing involving 20 tenth-grade PPLG students resulted in a feasibility percentage of 91.7%. Overall, the learning website achieved a feasibility score of 93.2%, indicating that it is highly feasible for use. Therefore, the chatbot AI-assisted learning website is suitable for use as a learning medium for Object-Oriented Programming in vocational high schools and has the potential to enhance students’ understanding and independent learning.